Efektivitas Minuman Kacang Hijau terhadap Peningkatan Kadar Hemoglobin Remaja Putri di Panti Asuhan di Kota Pekanbaru - Fachriani Putri; Riza Iriani Nasution (Jurnal Ilmu Kedokteran, 2018)
The complete mung bean’s phytochemicals composition help the hematopoiesis process increasing hemoglobin levels. Hemoglobin level is important as anemia sign. Anemia in adolescent girls might affect reproductive health. The aim of this study was to determine the effectiveness of mung beans compote to increase hemoglobin levels for adolescent girls at the Pekanbaru City Orphanage. This study was quasi-experimental study with one group pre test-post test design method. This study included 28 adolescent girls who had experienced menses and were not under any other medications. We used purposive sampling method to chose the subject. Hemoglobin levels were assessed pre and post oral administration of a cup mung bean compote 2 times a day for a week, each volume of 250 ml. The results were analyzed by paired t-test. We found that the average hemoglobin levels of adolescent girls are 13.13 g% and 13.14 g% respectively for pre and post treatment. Statistically, there was unsignificant effect of mung beans compote in increasing hemoglobin level (p = 0.97.